Pregnancy Outcomes of Women Hospitalized for Physical Assault, Sexual Assault, and Intimate Partner Violence - Auger, Nathalie (Journal of interpersonal violence, 2022)
Pregnancy outcomes of women with serious injuries due to violence receive limited attention. We examined the association of assault before and during pregnancy with maternal and infant outcomes at delivery. We performed a retrospective cohort study of 2,193,711 births in Quebec, Canada between 1989 and 2016. We identified women who were hospitalized for physical assault, sexual assault, and assault with documented intimate partner violence before and during pregnancy. We examined adverse outcomes at delivery, including preeclampsia, placental abruption, antepartum hemorrhage, stillbirth, preterm birth, low birthweight, and other disorders. In log-binomial regression models, we estimated risk ratios (RR) and 95% confidence intervals (CI) for the association between violence hospitalization and adverse birth outcomes, adjusted for potential confounders. Compared with no exposure, violence before or during pregnancy was associated with the future risk of placental abruption (RR 1.49, 95% CI 1.23?1.82), antepartum hemorrhage (RR 1.43, 95% CI 1.19?1.71), stillbirth (RR 1.83, 95% CI 1.27?2.63), preterm birth (RR 1.70, 95% CI 1.54?1.87), and low birthweight (RR 1.78, 95% CI 1.58?2.00). Physical assault, sexual assault, and assault with documented intimate partner violence were all associated with adverse outcomes. The risk of adverse outcomes was elevated regardless of timing and number of violence admissions, although associations were stronger for women hospitalized twice or more. Physical assault, sexual assault, and intimate partner violence are important risk factors for adverse pregnancy outcomes. Screening for violence in women of childbearing age and closer follow-up during pregnancy may help improve birth outcomes.